Obstacles and challenges of rural development in Afghanistan: examining problems and solutions - Yar, Fayaz Gul Mazloum; Zazia, Janat Gul (Jurnal Locus Penelitian dan Pengabdian, 2024)
This study investigates the multifaceted challenges hindering rural development in Afghanistan, employing an IMRAD structure to present findings. The introduction outlines the significance of rural development, noting that approximately 71% of the Afghan population resides in rural areas, predominantly engaged in agriculture. The methods section details a comprehensive document analysis and literature review from 2020 to 2024, focusing on institutional, socio-cultural, economic, environmental, and infrastructural barriers. Results indicate that ineffective governance, centralization, and socio-cultural issues such as gender inequality and low educational attainment severely impede progress. Additionally, economic challenges, including high poverty rates and unemployment, exacerbate the situation. Environmental concerns like land degradation and inadequate infrastructure further threaten rural livelihoods. The discussion emphasizes the interconnectedness of these challenges, advocating for a holistic approach that includes decentralization, community engagement, and investment in sustainable agricultural practices. The conclusion presents strategic recommendations for policymakers and stakeholders, highlighting the necessity of a coordinated, community-driven approach to achieve sustainable rural development in Afghanistan. By addressing these interconnected barriers, Afghanistan can foster long-term growth, stability, and improved quality of life for its rural populations.